Nutrição mineral e índices biométricos de copo-de-leite cultivado sob deficiência múltipla de nitrogênio e fósforo - Fernandes, Katiúcia Dias (2010)
A cut flowers production is one of the most significant segments of floriculture. The quality flowers production are related important aspects how mineral nutrition of ornamental plants. Multiple nutritional deficiencies is considered one of several factors that may introduce doubts in diagnosis based only on visual symptoms, hindering identification. Based on that, the objective of this work was to analyze the development of calla lily (Zantedeschia aethiopica) and their morphological changes resulting from nutritional disorders caused by multiple and simple omission of nitrogen and phosphorus in nutrient solution. Calla lily plants were cultured for a period of eight months in Hoagland and Arnon (1950), complete solution and with N omission, P omission, N and P omission and further nutrient solution with N and P concentration of 25%, 50%, and 75%, totalizing 7 treatments in 4 replicates and randomized experimental design. At the end of the experiment were evaluated the dry matter and plant growth, observing the height, shoot number, stem length and spate diameter, size of the rhizome and measures related to root development, besides the mineral composition of different plant parts. Plants that grown in solution with N omission did not produce inflorescences. They showed greater length, volume and density of roots when grown in a solution with P omission or 25 NP. The mineral contents present in roots and rhizomes was influenced by multiple omission of N and P, except N for roots.